2006
DOI: 10.1111/j.1467-9876.2006.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Double Hierarchical Generalized Linear Models (With Discussion)

Abstract: Summary. We propose a class of double hierarchical generalized linear models in which random effects can be specified for both the mean and dispersion. Heteroscedasticity between clusters can be modelled by introducing random effects in the dispersion model, as is heterogeneity between clusters in the mean model. This class will, among other things, enable models with heavy-tailed distributions to be explored, providing robust estimation against outliers. The h-likelihood provides a unified framework for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
583
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(587 citation statements)
references
References 134 publications
(201 reference statements)
2
583
0
2
Order By: Relevance
“…The square matrix of left-hand side of (3.4) is the negative Hessian matrix, H * = −∂ 2 h * /∂τ 2 , leading to an asymptotic variance of β (Lee and Nelder, 1996;Ha and Lee, 2003):…”
Section: Standard Estimation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The square matrix of left-hand side of (3.4) is the negative Hessian matrix, H * = −∂ 2 h * /∂τ 2 , leading to an asymptotic variance of β (Lee and Nelder, 1996;Ha and Lee, 2003):…”
Section: Standard Estimation Proceduresmentioning
confidence: 99%
“…For this we use the SCAD penalty. The h-likelihood (or hierarchical likelihood; Lee and Nelder, 1996) avoids such intractable integration and provides a statistically efficient procedure in random-effect models such as hierarchical GLMs (HGLMs; Lee and Nelder, 1996;Ha, 2008;Kim et al, 2011) and frailty models (Lee et al, 2006;Ha et al, 2010). The proposed method is illustrated using simulation studies and a well-known survival data, i.e.…”
mentioning
confidence: 99%
“…Lee and Nelder [1996] developed a systematic likelihood inference for HGLMs by using the h-likelihood. By eliminating some of the parameters from the h-likelihood, we can have two forms of profile likelihoods: (1) the classical marginal likelihood, and (2) the adjusted profile likelihood.…”
Section: H-likelihood Proceduresmentioning
confidence: 99%
“…Lee and Nelder [1996] observed that although in general a joint maximization of h-likelihood does not provide marginal MLEs for b, the deviance differences constructed from h and p b (h) are often very similar, so that they proposed using h for estimating b. However, with sparse binary data, the use of h for estimating b results in a nonignorable bias.…”
Section: H-likelihood Proceduresmentioning
confidence: 99%
See 1 more Smart Citation